Factors that Influence Adolescent's Attitude to Plan A Family Life - Willa Follona; Nessi Meilan; Delmaifanis Delmaifanis (Jurnal Ilmu dan Teknologi Kesehatan, 2020)
Adolescents are an age group between 10 and 19 years old, which is the transition period from childhood to adulthood. Adolescence is the capital of the nation's future development, so it must prepare to achieve its goals by planning a family life. However, there are still many teenagers who behave unhealthily, the percentage of young marriages and divorce rates is relatively high. Family life planning for an adolescent is urgently needed to prepare for future family life. The purpose of this research is to examine factors that affect family life planning in students. The research uses analytical survey methods with a cross-sectional approach. The study subjects were new students of Health Polytechnic of Jakarta 3 with a sample of 81 respondents taken using simple random sampling techniques. The results showed a relation between adolescent knowledge (p-value 0.000) and information sources (p-value 0.043) and attitudes towards family life planning. In contrast, maternal education (p-value 0.096) and family economy level (p-value 0.654) were not related to adolescent attitudes. This study concludes a significant relationship between knowledge and resources and attitudes towards family life planning for adolescents. To related parties such as schools, social institutions in the community, and health workers are expected to provide information about Family Life Planning for Adolescents more intensively.